ChemInform Abstract: Palladium‐Catalyzed Chelation‐Assisted ortho‐Tetra‐acetoxylation of 1, 3‐Diarylpyrazoles and 1, 3‐Diarylindazoles. Issue 4 (January 2015) - Kim, Se Hee; Lee, Sangku; Yu, Jin; Kim, Jae Nyoung
Abstract The palladium catalyzed reaction of 1, 3‐diaryl substituted heterocycles (I) and (IV) with diacetoxyiodobenzene provides the corresponding ortho tetra acetoxylated derivatives (III) regioselectively.